PRAGMATIC ASPECTS IN ROLE-PLAY ACTIVITY IN TEACHING SPEAKING - Dini Kurnia Irmawati (Fakultas Ilmu Budaya, Universitas Brawijaya, 2019)
To accommodate meaningful students’ speaking activity with the situation that can create communicative atmosphere, include pragmatic features, and arise motivation, role play is highly proposed due to its salient features. This paper aims to explain what kinds of pragmatic aspects that can be found in role-play activity and how pragmatic insight can be inserted in classroom activities in the context of TEFL (Teaching English as a Foreign Language), particularly in developing students’ speaking skill. This study is limited in the context of TEFL for Senior High School students. The findings show that the pragmatic aspects which can be found in role-play activities include maxim of quantity (be as informative as needed), maxim of quality (give true contribution), maxim of relevance (be relevant), and maxim of manner (avoid ambiguity and be orderly), turn-taking, and adjacency pairs. The ways how to teach role-play based on the pragmatic aspects are also presented in this study.